2004
DOI: 10.1007/s11240-004-4609-1
|View full text |Cite
|
Sign up to set email alerts
|

Response to increasing rates of boron and NaCl on shoot proliferation and chemical composition of in vitro kiwifruit shoot cultures

Abstract: The in vitro response of kiwifruit (Actinidia deliciosa) to increasing concentrations of boron (B) and NaCl in the culture medium was studied. Kiwifruit shoot cultures were grown in vitro for 12 weeks on an MS medium containing two B concentrations (0.1 and 2 mM) combined with five NaCl concentrations (0, 10, 20, 40 and 80 mM). Kiwifruit produced the longest shoots with 2 mM B when NaCl concentration was 0-20 mM. More shoots were produced with 2 mM B for all NaCl treatments. More shoots were produced with 2 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
5
3
1
Order By: Relevance
“…Among the different NaCl concentrations applied, 30 mM NaCl did not significantly reduce the productivity of the explants, and produced significant increases of the fresh and dry weights with respect to 0 mM NaCl. Similar results have been observed in other woody species (Singh et al, 2000;Sotiropoulos and Dimassi, 2004). Flowers and Läuchli (1983) reported that, at low concentrations, NaCl exerts a significant positive effect on shoot proliferation in vitro due to the increased osmolarity.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Among the different NaCl concentrations applied, 30 mM NaCl did not significantly reduce the productivity of the explants, and produced significant increases of the fresh and dry weights with respect to 0 mM NaCl. Similar results have been observed in other woody species (Singh et al, 2000;Sotiropoulos and Dimassi, 2004). Flowers and Läuchli (1983) reported that, at low concentrations, NaCl exerts a significant positive effect on shoot proliferation in vitro due to the increased osmolarity.…”
Section: Resultssupporting
confidence: 85%
“…This pattern, the result of increasing NaCl in the medium, is a common and expected in vitro response and has been reported for many species (Sotiropoulos, 2007;Sotiropoulos and Dimassi, 2004). For plants with a poor ability to exclude saline ions, marked injury in older leaves can occur within days (Munns, 2002).…”
Section: Effect Of Nacl On the Mineral Content Of Explantssupporting
confidence: 60%
“…However, Fe and Cu concentrations of explants were not significantly affected by NaCl levels in the culture media (Table 3). These results are in parallel to those of Sotiropoulos and Dimassi (2004) and Shiyab et al (2003) who worked with kiwifruit and sour orange shoots in vitro, respectively. In contrast increasing NaCl concentration in the growth medium raised Zn acquisition significantly (Table 3).…”
Section: ⎯⎯⎯⎯supporting
confidence: 81%
“…The observed increase in Na + and Cl -concentrations, as the result of NaCl salinity, is a common and expected response and has been also reported for many species (Sotiropoulos and Dimassi 2004;Sotiropoulos 2007). On the contrary, sweet cherry rootstock Gisela-5 presented unaffected or reduced Cl concentration under NaCl stress leading to the suggestion that the explants excluded Cl effectively.…”
Section: Discussionsupporting
confidence: 70%